Development of persistent gastrointestinal S. aureus carriage in mice - Flaxman, A; van Diemen, P; Yamaguchi, Y; Allen, E; Lindemann, C; Rollier, C; Milicic, A; Wyllie, D (Nature Publishing Group, 2017)
One fifth to one quarter of the human population is asymptomatically, naturally and persistently colonised by Staphylococcus aureus. Observational human studies indicate that although the whole population is intermittently exposed, some individuals lose S. aureus rapidly. Others become persistent carriers, as assessed by nasal cultures, with many individuals colonised for decades. Current animal models of S. aureus colonisation are expensive and normally require antibiotics. Importantly, these animal models have not yet contributed to our poor understanding of the dichotomy in human colonisation status. Here, we identify a single strain of S. aureus found to be persistently colonising the gastrointestinal tract of BALB/c mice. Phylogenetic analyses suggest it diverged from a human ST15 lineage in the recent past. We show that murine carriage of this organism occurs in the bowel and nares, is acquired early in life, and can persist for months. Importantly, we observe the development of persistent and non-persistent gastrointestinal carriage states in genetically identical mice. We developed a needle- and antibiotic-free model in which we readily induced S. aureus colonisation of the gastrointestinal tract experimentally by environmental exposure. Using our experimental model, impact of adaptive immunity on S. aureus colonisation could be assessed. Vaccine efficacy to eliminate colonisation could also be investigated using this model.